Anonymous
Anonymous asked in Science & MathematicsMathematics · 4 weeks ago

PLEASE HELPPP!!!!!!?

If f(x)=4(^3-2x) , determine the value of:

f(2+x)f(2-x)

3 Answers

Relevance
  • 4 weeks ago

    f(2 + x)f(2 - x) 

    = 4^[3 - 2(2 + x)]*4^[3-2(2 - x)]

    = 4^[3 - 4  - 2x] * 4^[3 - 4 + 2x]

    =4^(-1 - 2x) * 4^(-1 + 2x)

    =4^[ - 1 - 2x - 1 + 2x)

    =4^-2

    =1/4^2

    =1/16 Answer//

    • Commenter avatarLog in to reply to the answers
  • ?
    Lv 7
    4 weeks ago

    // There's a typo in your equation: f(x)=4(^3-2x)

    // Assuming you mean f(x) = 4³⁻²ˣ then

    f(x) = 4³⁻²ˣ

    f(2+x) = 4³⁻²⁽²⁺ˣ⁾ = 4⁻¹⁻²ˣ

    f(2-x) =  4³⁻²⁽²⁻ˣ⁾ = 4⁻¹⁺²ˣ

    So,

    f(2+x) f(2-x) = 4⁻¹⁻²ˣ 4⁻¹⁺²ˣ = 4⁻² = ¹⁄₁₆...............ANS

    • Commenter avatarLog in to reply to the answers
  • Ash
    Lv 7
    4 weeks ago

    f(x) = 4^(3-2x)

    f(2+x) = 4^(3 - 2(2+x)) = 4^(3-4-2x) = 4^(-1-2x)

    f(2-x) =  4^(3 - 2(2-x)) = 4^(3-4+2x) = 4^(-1+2x)

    f(2+x)f(2-x) = [4^(-1-2x)][4^(-1+2x)] = 4^(-1-2x+(-1+2x)) = 4⁻² = 1/16

    • Commenter avatarLog in to reply to the answers
Still have questions? Get answers by asking now.